Isolation of a novel Bacillus subtilis HF1 strain that is rich in lipopeptide homologs and has strong effects on the resistance of plant fungi and growth improvement of broilers - Li, Qianru; Wang, Ying; Chen, Chao; Zeng, Mingbai; Jia, Qingyun; Ding, Jinhao; Zhang, Chenjian; Jiao, Shanhai; Guo, Xupeng; Wu, Jihua; Fan, Chengming; Chen, Yuhong; et al. (Frontiers in Microbiology, 2024)
Bacillus subtilis is an important probiotic microorganism that secretes a variety of antimicrobial compounds, including lipopeptides, which are a class of small molecule peptides with important application value in the fields of feed additives, food, biopesticides, biofertilizers, medicine and the biological control of plant diseases. In this study, we isolated a novel B. subtilis HF1 strain that is rich in lipopeptide components and homologues, has a strong antagonistic effect on a variety of plant fungi, and is highly efficient in promoting the growth of broilers. The live B. subtilis HF1 and its fermentation broth without cells showed significant inhibitory effects on 20 species of plant fungi. The crude extracts of lipopeptides in the fermentation supernatant of B. subtilis HF1 were obtained by combining acid precipitation and methanol extraction, and the lipopeptide compositions were analysed by ultrahigh-performance liquid chromatography with quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS). The results showed that HF1 could produce 11 homologues of surfactin and 13 homologues of fengycin. Among the fengycin homologues, C13-C19 fengycin A and C15-C17 fengycin B were identified; among the surfactin homologues, C11-C17 surfactin A and C13-C16 surfactin B were characterized. C13 fengycin A, C11 surfactin A and C17 surfactin A were reported for the first time, and their functions are worthy of further study. In addition, we found that HF1 fermentation broth with and without live cells could be used as a feed additive to promote the growth of broilers by significantly increasing body weight up to 15.84%. HF1 could be a prospective strain for developing a biocontrol agent for plant fungal diseases and an efficient feed additive for green agriculture.